Drawing to reason and learn in science. Issue 2 (9th August 2019) - Tytler, Russell; Prain, Vaughan; Aranda, George; Ferguson, Joseph; Gorur, Radhika
Abstract: Despite mixed results in research on student learning from drawing in science, there is growing interest in the potential for this visual mode, in tandem with other modes, to enact and enable student reasoning in this subject. Building on current research in this field, and using a micro‐ethnographic approach informed by socio‐semiotic perspectives, we aimed to identify how and why student drawing can contribute to student reasoning and learning. In our study, secondary school students were challenged to explore and collaboratively create explanatory representations of phenomena including through drawing. Data were generated using multiple wall‐ and ceiling‐mounted cameras capable of continuously tracking groups of students negotiating these representational challenges. Our analysis proceeded through active and iterative viewing of the extensive video record, and the identification of themes to establish possible relationships between drawing and reasoning. Through this process, we (a) identify multiple necessary conditions and varied opportunities for student drawing to enact and enable reasoning, and (b) extend current understandings of how the particular affordances of this mode interact with these conditions to contribute to student learning in science.